PENGARUH MOTIVASI DAN KOMITMEN TERHADAP KINERJA PEGAWAI PELAYANAN DAN PERAWATAN RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Enando, Adel Putra; Sakdanur, Sakdanur; Kartikowati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the effect of motivation of and commitment toward employee performance at the unit of services and treatments. This research is conducted at the Mental Hospital Tampan Riau Province from April to June 2014 The method used is descriptive quantitative method. The population is all employees and treatment services Mental Hospital Tampan. 30 respondents are selected by random sampling technique. The data collection instrument used is a questionnaire for the dependent variables: performance (Y); independent variables: motivation (X1), and commitment (X2). The data analysis technique used is multiple linear regression statistical techniques. From the results, it can be concluded that: (1) motivational effect on employee performance and maintenance services Mental Hospital Tampan; (2) commitment effect on employee performance and maintenance services Mental Hospital Tampan; (3) the effect of the influence of motivation and commitment to employee performance and maintenance services Mental Hospital Tampan amounted to 29.7%. Keywords: motivation, commitment, performance